Pengembangan Game Edukasi Pengenalan Hutan Bakau Mangrove Ngurah Rai Berbasis Android - Kadek Surya Adi Saputra; I Made Oka Widyantara (Ikatan Ahli Informatika Indonesia, 2024)
Mangrove forests in Ngurah Rai have a very important ecological role, but public awareness of their existence and benefits is still low. This research aims to develop an android-based educational game that introduces mangrove forests to the community, especially the younger generation and tourists. The method used in this educational game application is waterfall or called system development life cycle (SDLC). This application testing stage uses the white box testing method with the base path technique of calculating the number of scenarios carried out by the user and black box testing for application functionality testing. It is hoped that this educational game can be an interesting tool to support environmental conservation efforts and increase community involvement in mangrove forest conservation and also contribute to the development of innovative learning media that integrate technology and environmental education